Discectomy-Related Information on the Internet. Issue 2 (15th January 2015) - Elhassan, Yahya; Sheridan, Gerard; Nassiri, Mujtaba; Osman, Mugtaba; Kiely, Pat; Noel, Jacques
<x xml:space="preserve">Abstract</x> Study Design. A quality-control Internet-based study using recognized quality-scoring systems. Objective. To evaluate the quality of information available on the Internet. Summary of Background Data. Quality of health information on the Internet is of much concern and the emphasis for appraisal of Internet Web sites is needed. This study is to determine if it has improved with the surge in Internet usage. Methods. The 3 most commonly used search engines were identified and a search for "Discectomy" was performed on each. Two reviewers categorized the Web sites according to their types and the quality of each was assessed using recognized scoring systems including the Journal of the American Medical Association (JAMA) benchmark, DISCERN score, and discectomy-specific content score. The quality of the information was also assessed according to the presence and absence of the Health on the Net code. Results. Fifty-three Web sites were identified, and analyzed. Commercial Web sites were predominant, 24 of them were identified, 7 were governmental, 6 were produced by physicians, none were produced by allied health professionals, 3 were academic, 4 were public health information Web sites, 4 were attached to social media and discussion groups, 3 were related to media, and 2 were unspecified. Internet sites with a Health on the Net code demonstrated significantly higher quality than those without the code (P < 0.0001). Public health information Web sites attained the highest overall DISCERN and discectomy-specific scores followed by Web sites of the government and nonprofit organizations. Conclusion. The overall quality of information regarding discectomy remains poor and variable despite an exponential increase in the number of users and Web sites, with a slight trend toward improvement, only 20% to 30% are of good quality, compared with that 10 years ago (<10%). Presence of Health on the Net code is a very reliable marker for health information quality. Level of Evidence: 3